INTEGRATION OF ISLAMIC RELIGIOUS EDUCATION AND SCIENCE LEARNING IN ELEMENTARY SCHOOL - Mauhibur Rokhman; Fathul Amami (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The focus of this article is to discuss the implementation of the integration of Islamic religious education and science in learning at the Nahdhatul Ulama Elementary School, Padomas, Jember Regency. The type of research used is qualitative with a case study approach. Sources of data obtained from primary data and secondary data. Data collection techniques are observation, interviews and documentation. The results of this study are the integration of Islamic Religious Education and Science in learning at SD Nahdhatul Ulama Padomasan, Jember Regency, which is divided into three stages, a) Learning planning is prepared before carrying out learning, identifying basic competencies (KD) and then pouring them into a lesson plan. b) The teacher conducts preliminary activities, then conveys to students what activities will be carried out according to the theme, students are directed to explore and find out for themselves what they are learning. c) Evaluation is carried out after each lesson by providing LKPD, mid-semester evaluation and end-semester evaluation.Keywords: Islamic Religious Education; Integration of Islam and Science; Elementary School. AbstrakFokus artikel ini ialah implementasi integrasi pendidikan agama Islam dan sains dalam pembelajaran di Sekolah Dasar Nahdhatul Ulama Padomasan Kabupaten Jember. Jenis penelitian yang digunakan adalah kualitatif dengan pendekatan study kasus. Sumber data diperoleh dari data primer dan data skunder. Teknik pengumpulan data yaitu observasi, wawancara dan dokumentasi. Hasil dari penelitian ini adalah Integrasi Pendidikan Agama Islam dan Sains dalam pembelajaran di SD Nahdhatul Ulama Padomasan Kabupaten Jember terbagi menjadi tiga tahapan, a) Perencanaan pembelajaran disusun terlebih dahulu sebelum melaksanakan pembelajaran, mengidentifikasi KD kemudian menuangkannya dalam RPP. b) Guru melakukan kegiatan pendahuluan, kemudian menyampaikan ke peserta didik kegiatan apa yang akan dilakukan sesuai dengan tema, peserta didik diarahkan untuk mengeksplorasi dan menemukan sendiri apa yang diepalajari. c) Evaluasi yang dilakukan setiap selesai pembelajaran dengan memberikan LKPD, evaluasi tengah semester dan evaluasi akhir semester. Kata Kunci: Pendidikan Agama Islam; Integrasi Islam dan Sains; Sekoah Dasar.